Origens dos cromossomos B em espécies de Characidium (Characiformes, Crenuchidae) baseada em pintura cromossômica, sequências de rDNA e histonas - Serrano, Érica Alves [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
B or supernumerary chromosomes are extra elements to the standard set A and are present in several groups of eukaryotes, such as plants, fungi and animals. They may have different origins, including derivation of autosomal or sex chromosomes and even by interspecific crosses, which make them as an interesting model for genetic and evolutionary studies. The advent of chromosome microdissection technique, a method that allows the direct isolation of DNA from any region cytogenetically recognized, has provided new information on the structure and composition of these genomic elements in a significant number of organisms. In this sense, the present work was developed aiming to analyze the B chromosomes present in three fish species of the genus Characidium through classical and molecular cytogenetic techniques involving microdissection of B and sex chromosomes associated with the FISH technique, as well as fluorescent in situ hybridization of 18S and 5S ribosomal DNAs and genes for the H3 and H4 histones. Additionally, these repetitive DNA sequences were amplified, cloned and sequenced from genomic DNA of individuals without B chromosomes and from B chromosomes DNA microdissected. The results obtained by chromosome painting confirmed that the ZW sex chromosomes have a single origin in this group, while the B chromosomes have two types of origin. In C. gomesi and C. pterostictum, B chromosomes apparently exhibit an intraspecific origin, related to sex chromosomes, but, considering the placement of these species in the phylogeny established, in independent events. Moreover, in C. oiticicai these elements might have had an interspecific origin, possibly related to some sort of hybridization by introgression. The presence of histone sequences and 5S rDNA in B chromosomes evidenced by physical mapping and PCR amplification, as well as low genetic divergence, indicate a common ancestry between sequences present in B chromosomes of C. gomesi ...

Cromossomos B ou supranumerários são elementos extras ao conjunto padrão A e estão presentes em vários grupos de eucariotos, como plantas, fungos e animais. Podem ter origens distintas, incluindo derivação do conjunto autossômico ou de cromossomos sexuais e até mesmo por cruzamentos interespecíficos, o que os caracterizam como um interessante modelo para estudos genéticos e evolutivos. O advento da técnica de microdissecção cromossômica, método que possibilita o isolamento direto do DNA de qualquer região citogeneticamente reconhecida, tem proporcionado avanços no conhecimento da estrutura e composição destes elementos genômicos em um número significativo de organismos. Neste sentido, o presente trabalho foi desenvolvido com o objetivo de analisar os cromossomos B presentes em três espécies de peixes do gênero Characidium, através de técnicas citogenéticas clássicas e moleculares, envolvendo microdissecção dos cromossomos Bs e sexuais, associada à técnica de FISH, assim como hibridação fluorescente in situ dos DNAs ribossômicos 5S e 18S e DNAs histônicos H3 e H4. Adicionalmente, estas sequências de DNA repetitivo foram amplificadas, clonadas e sequenciadas a partir do DNA genômico de indivíduos sem cromossomos B e do DNA dos cromossomos B microdissecados. Os resultados obtidos pela pintura cromossômica confirmam que os cromossomos sexuais ZW possuem uma origem única neste grupo, enquanto os cromossomos B possuem dois tipos de origem. Em C. gomesi e C. pterostictum, os cromossomos B apresentam origem intraespecífica, relacionada aos cromossomos sexuais, mas independentes, considerando o posicionamento destas espécies na filogenia estabelecida. Por outro lado, em C. oiticicai esses elementos podem ter tido uma origem interespecífica, possivelmente relacionada a algum tipo de hibridação introgresiva. A presença de sequências histônicas e de DNAr 5S nos cromossomos B evidenciada pelo mapeamento ...
Keywords: Peixe - Genetica; Citogenética animal; Cromossomos; DNA; Genetica animal; Melhoramento genetico; Animal genetics